Environmentally friendly chemical synthesis of intermetallic iron aluminide submicrometer particles. (20th September 2021) - Kobayashi, Yasukazu; Teah, Heng Yi; Hanada, Nobuko
Abstract: Intermetallic iron aluminide (FeAl) in the submicrometer range is an emerging material for industrial applications due to its improved ductility and enhanced properties. In addition, preparing high-surface-area FeAl powder is highly desired due to its catalyst applications. The chemical synthesis of FeAl is feasible for mass production. However, previous synthesis methods require extensive use of toxic chemicals, organic solvents, and specialized environment-controlled facilities. To achieve a cleaner synthesis of FeAl powder with a high surface area, herein, we propose a new synthesis route. First, an Fe–Al oxide precursor, FeAl2 O4, was prepared from iron and aluminum nitrates. Then, the oxide precursor was reduced to FeAl using CaH2 in molten LiCl at 600°C–700 °C. The reduction at 700 °C resulted in a single-phase intermetallic FeAl without any impurity phase, whereas at 600 °C and 650 °C, a trace of Al(OH)3 was detected under X-ray diffraction, indicating an incomplete reduction. N2 adsorption–desorption analyses and scanning and transmission electron microscopy with energy-dispersive X-ray spectroscopy confirmed the formation of submicrometer FeAl particles. The surface area of the prepared FeAl powder was as high as 88 m 2 /g, which is three times higher than that reported for Fe3 Al nanoparticles prepared via a physical approach. We further performed a screening-level lifecycle assessment to evaluate the prospective environmental impact of the FeAl synthesis route. The cumulative energy demand and global warming potential associated with 1-kg-FeAl synthesis were 566 MJ and 41 kg CO2 e, respectively, which are about half of those for existing LiAlH4 -based methods. Therefore, the proposed synthesis route is promising for environmentally friendly synthesis of FeAl particles. Highlights: Chemical synthesis of intermetallic FeAl from oxide precursors at 600–700 °C. Preparation of highly pure intermetallic FeAl submicrometer particles (47–76 nm). Environmental-friendliness of the proposed method evaluated using LCA.